Spectrofluorimetric and Spectrophotometric Methods for the Determination of Ciprofloxacin HCl and Their Comparison with the Compendial High-Performance Liquid Chromatography (HPLC) Method - Khan, Marium Fatima; Sheraz, Muhammad Ali; Ahmed, Sofia; Anwar, Zubair; Ahsan, Syed Furqan; Sabah, Arif; Ali, Raahim; Kazi, Sadia Hafeez (Anti-Infective Agents, 2026)
IntroductionCiprofloxacin hydrochloride (CH) is a widely used fluoroquinolone antibiotic. Accurate, cost-effective methods are essential for its routine quality control. This study aimed to develop and validate simple UV spectrophotometric and spectrofluorimetric methods for quantifying CH in bulk and pharmaceutical formulations.MethodsUV analysis was performed at 271 nm, while fluorescence measurements were taken at 335 nm (excitation) and 416 nm (emission) in phosphate buffer (pH 7). Validation was conducted in accordance with the International Council for Harmonisation (ICH) guidelines for linearity, accuracy, precision, Limit of Detection (LOD), Limit of Quantification (LOQ), robustness, and solution stability. Results were compared with an official HPLC method.ResultsBoth methods demonstrated excellent linearity in the range of 0.4-2.0 × 10-5 M (r2 = 0.9999). The limits of detection (LOD) and quantification (LOQ) were 0.64/1.95 × 10-6 M for the UV method and 0.66/1.99 × 10-6 M for the fluorescence method. Recovery values ranged from 99.27% to 99.92% (UV) and 98.60% to 100.32% (fluorescence), with %RSD values below 2%, indicating good precision. Robustness testing revealed minimal effects from deliberate variations in experimental conditions, and the results showed strong agreement with the compendial HPLC method.DiscussionUV spectrophotometric and spectrofluorimetric methods proved to be accurate, sensitive, and reproducible. The UV method is ideal for basic lab setups, while fluorescence offers greater sensitivity for lower concentrations. Comparable results with HPLC confirm their suitability.ConclusionValidated UV and fluorescence methods provide efficient, accurate, and low-cost alternatives to HPLC for quality control of CH in pharmaceutical analysis.
Keywords: ciprofloxacin HCl